Evaluation of 2-point, 3-point, and 6-point Dixon magnetic resonance imaging with flexible echo timing for muscle fat quantification - Grimm, Alexandra; Meyer, Heiko; Nickel, Marcel D.; Nittka, Mathias; Raithel, Esther; Chaudry, Oliver; Friedberger, Andreas; Uder, Michael; Kemmler, Wolfgang; Quick, Harald H.; Engelke, Klaus (European Journal of Radiology, 2018)
The purpose of this study is to evaluate and compare 2-point (2pt), 3-point (3pt), and 6-point (6pt) Dixon magnetic resonance imaging (MRI) sequences with flexible echo times (TE) to measure proton density fat fraction (PDFF) within muscles. Two subject groups were recruited (G1: 23 young and healthy men, 31 ± 6 years; G2: 50 elderly men, sarcopenic, 77 ± 5 years). A 3-T MRI system was used to perform Dixon imaging on the left thigh. PDFF was measured with six Dixon prototype sequences: 2pt, 3pt, and 6pt sequences once with optimal TEs (in- and opposed-phase echo times), lower resolution, and higher bandwidth (optTE sequences) and once with higher image resolution (highRes sequences) and shortest possible TE, respectively. Intra-fascia PDFF content was determined. To evaluate the comparability among the sequences, Bland-Altman analysis was performed. The highRes 6pt Dixon sequences served as reference as a high correlation of this sequence to magnetic resonance spectroscopy has been shown before. The PDFF difference between the highRes 6pt Dixon sequence and the optTE 6pt, both 3pt, and the optTE 2pt was low (between 2.2% and 4.4%), however, not to the highRes 2pt Dixon sequence (33%). For the optTE sequences, difference decreased with the number of echoes used. In conclusion, for Dixon sequences with more than two echoes, the fat fraction measurement was reliable with arbitrary echo times, while for 2pt Dixon sequences, it was reliable with dedicated in- and opposed-phase echo timing.
EVALuna2:34695